2017
DOI: 10.1177/0961203317696591
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation for end-stage renal disease in lupus nephritis, a very safe procedure: a single Latin American transplant center experience

Abstract: Background Lupus nephritis (LN) is one of the most frequent complications of SLE and occurs in up to 50% of cases depending on the studied population. Of these, approximately 20% progress to end-stage renal disease (ESRD), with the treatment of choice being a kidney transplant. Objective The objective of this study was to describe the clinical outcome of patients transplanted due to LN, compared with patients transplanted for other causes, in a Latin American population from the Fundación Valle del Lili in Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…Accordingly, 17 studies were included in the pooled analysis. 7,912,1526
Figure 2Flow diagram of literature search and study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, 17 studies were included in the pooled analysis. 7,912,1526
Figure 2Flow diagram of literature search and study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…We could not identify a similarly large study of patients with LN-ESRD who were eligible to have a kidney transplant. Although several studies with small sample sizes (patients with LN-ESRD who had a transplant: n = 40 [32], n = 65 [14], and n = 17 [13]) also suggested the potential benefits of renal transplant in this population, their comparison groups were treated with long-term peritoneal dialysis or hemodialysis regardless of eligibility for a transplant. As such, these studies have been highly vulnerable to confounding by contraindication because sicker patients tend to continue long-term dialysis without moving to a transplant waitlist (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with LN-ESRD may have a heightened risk for certain posttransplant complications (10,11), including infections partly attributed to extensive pretransplant immunosuppression, graft thrombosis related to antiphospholipid antibody syndrome, and recurrent LN affecting the allograft (12). Furthermore, although small-scale studies have reported improved survival for patients who have a transplant compared with those who continue to receive dialysis (13,14), these studies were confounded by indication, because healthier patients had a transplant. As such, the potential survival benefit associated with renal transplant remains unclear among patients with LN-ESRD.…”
Section: Primary Funding Source: National Institutes Of Healthmentioning
confidence: 99%
“…146 Clinically significant LN posttransplant recurs in <20% of patients. [147][148][149][150][151] Patients should remain on hydroxychloroquine posttransplant and be on MMF/ CNI-based immunosuppressive regimen. Patients with mild flares can be treated with oral corticosteroids alone.…”
Section: Special Circumstancesmentioning
confidence: 99%